Influence of customer values and self-image congruity on customer behavior based CRM performance - Mandy Loh; Maisarah Ahmad; Syed Shah Alam (2015)
The purpose of this study is to investigate the influence of the key dimensions of customer value (functional value, emotional value, social value, and perceived sacrifice) and self-image congruity on customer-behavior based CRM performance. The study also attempts to investigate on the effect of key dimensions of customer value and self-image congruity on customer satisfaction and brand loyalty. The research model for this study was adopts an integrated framework from a previous study, and adds new element into it. This study has chosen to examine the framework in the retail industry, specifically hypermarket in Malaysia, where the adoption of CRM tools is increasing incrementally. The study target on the Generation Y who believed will be the future driver of retail industry. The findings show that perceived sacrifice appears to be a critical customer perceived value in influencing the customer behavior-based CRM performance and customer satisfaction. This study show that brand loyalty would directly influence the customer behavior-based CRM performance. Perceived sacrifice and brand loyalty should be focused when trying to improve the performance of CRM.